Violent Communication in the Household upon Muslim Women in Maluku - nfn sulaeman; La Jamaa; Mahdi Malawat (Jurnal Pekommas, 2019)
Violent communication in the household is the act of an abnormal communication of the husband on the wife that brings up the inconvenience of harmonious households. This study aimed to describe the motives, purport, and acceptance of in household violence treatment experienced by Muslim women in the Maluku. The research method used was the phenomenology that focused on purport study. This research used a qualitative approach based on the constructivist paradigm.  The data was collected through in-depth interviews and observations of the ten married Muslim women in Maluku. They were chosen by snowball sampling technique. The result showed that the in hosehold violence for Muslim women in Maluku have a "because" motive, such as: adultery, polygamy, communication barriers, disobedience of wife-husband fulfills its obligations, default character, unemployment, social patriarchy, economic dependency, neglect, the fulfillment of economic, religious, as well as social solidarity, and the " in order to" motive, such as: problem-solving, cover the shortage of husband, feeling happy on conquering women, as well as responsibility. The meaning of the in household violence experienced showed physical violence, psychological, economic, and sexual violent.